Towards sustainable, solution-processed organic field-effect transistors using cashew gum as the gate dielectric - Faraji, Sheida; Tall, Abdoulaye; Mohammadian, Navid; Seck, Mané; Saadi, Meriem; Tavasli, Aybüke; Erouel, Mohsen; Khirouni, Kamel; Diallo, Abdou Karim; Majewski, Leszek A. (Frontiers in Materials, 2023)
Towards sustainable, solution-processed organic field-effect transistors using cashew gum as the gate dielectric"We would like to thank you for considering publication of our article in your journal. We have revised our paper in response to the reviewer's comments as follows:The manuscript explores the application of cashew gum as an organic gate dielectric in solution-processed organic field-effect transistors (OFETs). The authors have presented an informative introduction to organic field-effect transistors, emphasizing the significance of choosing an appropriate gate dielectric to enhance transistor performance. Notably, the authors opted for a biopolymer dielectric over synthetic polymer dielectrics, adding an interesting dimension to the research. The experimental details provided are comprehensive, enabling replication of these studies for future research endeavors. Additionally, the results and discussion section extensively integrates relevant data, leading to a thorough discussion that directly addresses the problem statement outlined in the introduction.1. Authors have chosen DPPTTT:PMMA is chosen for the semiconductor layer. Is there any specific reason? There are few organic p-type polymers with higher mobility, which can be used to enhance the overall mobility of OFETs with CG.